The uses of the past in the early Middle Ages - Hen, Yitzhak; Innes, Matthew (Cambridge University Press, 2000)
This is the first book to investigate how people in the early middle ages used the past: to legitimate the present, to understand current events, and as a source of identity. Each essay examines the mechanisms by which ideas about the past were - sometimes - subtly reshaped for present purposes.